THE EFFECT OF CIPLUKAN (Physalis angulata L.) FRUIT EXTRACT ON SGPT AND SGOT LEVELS AGAINST WHITE MALE MICE (Mus musculus) HYPERGLYCEMIA INDUCED BY ALLOXAN AS BIOLOGY LEARNING RESOURCES - Fitri, Nur Lailatul; Susetyarini, Roro Eko; Waluyo, Lud (University of Muhammadiyah Malang, 2016)
Ciplukan (Physalis angulata L.) used by the community as an antidiabetic drug. Antidiabetic effects caused ciplukan fruit of this plant contain chemicals flavonoids with the percentage of fruit extract 300 mg / ml was 84%. Flavonoids are antioxidant compounds one that works a treat or neutralize free radicals that are expected with the administration of these antioxidants can be inhibited damage to body cells and can prevent damage to the body and the onset of degenerative diseases. This type of research is True Experimental Research. The research design using The Posttest-Only Control Group Design. The research design used completely randomized design (CRD).Â This research data is data SGPT and SGOT levels. Analysis of data using one-way analysis of variance at significance level of 0.05 and Duncan 5%. The results showed that different doses of fruit extract ciplukan effect on SGPT and SGOT levels of mice. Duncan test showed that the treatment dose ciplukan fruit extract is the most effective dose of 2 ml / kg. The research results can be used by teachers as information of an alternative to utilize medical plants of hyperglicemia and antiocsidant on Biology subject for X Grade of Senior High School, especially on the concept Maintenance and Utilizing of Biological Diversity in Core Competence 4.